2018
DOI: 10.1007/s11892-018-1116-z
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Diabetes-Heart Failure Connection

Abstract: Purpose of the ReviewTo summarize current clinical data investigating the link between diabetes and heart failure pathophysiology, the association of glucose control with heart failure, and the impact of current antihyperglycemic drugs on heart failure.Recent FindingsAlthough heart failure is one of the most prevalent outcomes occurring in real life and cardiovascular outcome trials, insufficient attention was given to this condition in diabetes research over the last decades. With both beneficial and detrimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 132 publications
(127 reference statements)
1
2
0
2
Order By: Relevance
“…Figure 6 lists the different explanatory variables according to their contribution to each model. We can observe that the clinical characteristics of Platelets, Glucose, Blood Urea Nitrogen, Age, Heart Rate, Systolic Blood Pressure, and Diastolic Blood Pressure are important factors influencing the prediction of HF, and previous studies of HF Similar results have been found in previous studies of HF [ 74 , 75 , 76 ]. However, the effects of GCS eye, GCS motor, GCS verbal, Red Blood Cell, International Normalized Ratio and Gender were not as significant.…”
Section: Resultssupporting
confidence: 84%
“…Figure 6 lists the different explanatory variables according to their contribution to each model. We can observe that the clinical characteristics of Platelets, Glucose, Blood Urea Nitrogen, Age, Heart Rate, Systolic Blood Pressure, and Diastolic Blood Pressure are important factors influencing the prediction of HF, and previous studies of HF Similar results have been found in previous studies of HF [ 74 , 75 , 76 ]. However, the effects of GCS eye, GCS motor, GCS verbal, Red Blood Cell, International Normalized Ratio and Gender were not as significant.…”
Section: Resultssupporting
confidence: 84%
“…"DC" is the term that is used for the presence of myocardial dysfunction in the absence of CV associated risk factors (Lehrke and Marx, 2017). The metabolism, function, and structure of the cardiac system may be affected by the underlying pathways of both diabetes and HF (Wallner et al, 2018). In the early stages of DC, structure and morphology changes are not considerable, but in the late stages, both systolic and diastolic function may be affected with greater increases in size and wall thickness of the left ventricular mass (Jia et al, 2016).…”
Section: Coexistence Of T2dm and Hfmentioning
confidence: 99%
“…Ide však o správy z observačných štúdií, kde je skreslenie spôsobené tým, že diabetici, čo užívajú inzulín, majú ťažšie formy SZ ako diabetici bez inzulínu. V každom prípade sa však nezdá, že by liečba inzulínom mala u diabetikov so SZ priaznivý vplyv na mortalitu (25).…”
Section: Manažment Diabetu Pri Srdcovom Zlyhávaníunclassified